Fabrication and characterization of electrospun porous cellulose acetate nanofibrous mats incorporated with capric acid as form-stable phase change materials for storing/retrieving thermal energy. Issue 12 (26th September 2017) - Zhang, Jin; Yang, Qiang; Cai, Yibing; Song, Xiaofei; Qiao, Hui; Zhang, Junhao; Wei, Qufu
ABSTRACT: Electrospun cellulose acetate (CA) nanofibrous mats incorporated with capric acid was studied to fabricate form-stable phase change materials (PCMs) for storing/retrieving thermal energy. Electrospun CA nanofibrous mats with different porous structures and specific surface areas were firstly prepared through regulating the volume ratio of mixture solvent of acetone/dichloromethane (DCM). Effects of different volume ratio of mixture solvent and mat thickness on the morphological structure, specific surface area, and absorption capacity of CA nanofibrous mats were systematically investigated. The results indicated that CA nanofibrous mats were highly porous on the surface; hence, they were capable of absorbing a large amount of capric acid. The maximum absorption capacity of CA mats via electrospinning with volume ratio of acetone/DCM being 5/5 was ~95.8 wt%, due to its higher specific surface area of ~17.1 m 2 /g. The specific surface area and capric acid absorption capacity of CA nanofibrous mats increased with the increases of mat thickness. As the thickness of nanofibrous mats increased from 10 to 85 μm, the corresponding specific surface area and capric acid absorption capacity of mats increased respectively from 7.2 to 29.0 m 2 /g and 92.1 to 98.5%. Morphological structures, as well as the properties of thermal energy storage and thermal insulation of the fabricated form-stable PCMs, were studied by scanning electron microscopy, differential scanning calorimetry, and measurement of freezing times, respectively. The results indicated that the resulting form-stable PCMs could well maintain their phase transition characteristics and demonstrated great thermal energy storage capability and temperature regulation ability.